Effects of spray-dried egg albumin on growth performance of early-weaned pigs - De La Llata, M.; Grinstead, G.S.; Woodworth, J.C.; Goodband, Robert D.; Tokach, Michael D.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Seventy two early-weaned pigs (initially 12.4 lb) were used in a 14-d growth trial to evaluate a control diet (no added spray-dried egg albumin or animal plasma) or the control diet with 5% spray-dried plasma, 7% spraydried egg albumin~ or 2.5% spray-dried plasma plus 3.5% spray-dried egg albumin. Pigs fed 5% spray-dried animal plasma had greater ADG and improved F/G compared with those fed 7% spray-dried egg albumin, whereas pigs fed the control or a blend of spray-dried egg albumin plus spray-dried animal plasma had intermediate performance. These results suggest that the spray-dried egg albumin used is not an effective replacement for spray-dried animal plasma in diets for early-weaned pigs.
Keywords: Swine; Spray-dried egg; Early-weaned pigs; Performance